2022
DOI: 10.4103/mjdrdypu.mjdrdypu_81_20
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Self-Medication Practices Among Students of Health-Care Professions in India

Abstract: The principles of medication management include storing, ordering, dispensing, and administration of the medications. Each of these steps is equally important to achieve the maximum benefits of the medicines. However, self-medication is common across the globe where these principles are severely compromised. Self-administration of medication is an approach in which an individual uses a medicine or drug to treat any symptoms or diagnosed disorder. It is an individual's initiative to take medicines without consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It is thought that the decrease in this number is probably due to the Iran’s policy for antibiotics and its prescription, which has been put in place recently [ 26 ]. Self-medication with antibiotics among students, which is more common among medical students, is a topic that many studies have investigated it [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the decrease in this number is probably due to the Iran’s policy for antibiotics and its prescription, which has been put in place recently [ 26 ]. Self-medication with antibiotics among students, which is more common among medical students, is a topic that many studies have investigated it [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to those reported by Kasulkar et al 6 Other authors have reported this prevalence among medical students within a wide range of 25% to 96%. 3,[7][8][9][10][11][12][13][14][15][16] Because of use of different criteria and reference periods in various studies, it is difficult to compare the overall prevalence among them. The present study found a significantly more prevalence of self-medication among female students as compared to males, which is in concordance with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…It's thought that the decrease probably was due to the Iran policy for antibiotics and prescribing pattern to limit the antibiotics recently (24). Self-medication with antibiotics in students is a topic that many studies have been done on it and is more common in medical students (25).…”
Section: Discussionmentioning
confidence: 99%